Modelling the three-stage activation process of composite sourdough starters developed using pumpkin and mung bean flours - Lau, Siew Wen; Chin, Nyuk Ling; Talib, Rosnita A.; Basha, Roseliza Kadir (Elsevier BV, 2024)
Sourdough greatly enhanced competitiveness and qualities of bakery products, particularly their texture that is manipulated by leavening. The potential of non-cereal involvement to boost properties of sourdough starters is still unexplored. This study hence targeted to improve leavening in wheat sourdough starters through three-stage activation system using pumpkin and mung bean flours. The suitability of Gompertz curve to describe the leavening was also investigated. Pumpkin and mung bean flours were respectively incorporated into wheat flour at 15% as composite flours to be developed as sourdough starters following a three-stage activation process via the conventional method of measuring leavening heights for volume analysis. The specific volume of sourdough starters using composite flours was improved by 41.1% with pumpkin flour and 52.1% with mung bean flour through the observed activation process when compared to control of using wheat flour alone. The volume expansion ratio was also accurately described using the Gompertz model, a mathematical model that compares leavening performances among different sourdough starters. The composite sourdough starters using pumpkin or mung bean with wheat flours gave great impacts to their leavening performances, especially in terms of the markedly risen maximum volume expansion ratio from 0.403 to 1.720 and 2.026 cm3/cm3 and reduced overall fermentation time from 18 to 7 and 8 h respectively following the three-stage activation process. Pumpkin and mung bean flours are highly potential in enhancing the leavening of wheat sourdough starters as observed in the three-stage activation and as shown by the accurate description of a typical growth curve using the Gompertz model.